THE INFLUENCE OF PROFITABILITY AND ACTIVITY ON FINANCIAL PERFORMANCE IN MINING COMPANIES REGISTERED IN INDONESIA STOCK EXCHANGE - Susiowati Susiowati; Sochib Sochib; Muhamad Ali (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2020)
This research was conducted with the aim to determine the effect of profitability and activity on financial performance in mining companies listed on the Indonesian stock exchange. Financial Performance is an illustration to find out the financial situation in a company for a certain period and analyzed with financial analysis tools. In assessing the financial performance of a company, it can use certain benchmarks. And usually the ratio is used. In this study, the calculation system used by researchers is to use profitability analysis tools (Net Profit Margin), activity (Inventory Turn Over) and performance (Return On Assets). The method used in this research is quantitative descriptive obtained by 17 samples of mining companies listed on the Indonesia Stock Exchange in the 2014-2017 period. Statistical test results in this study indicate that profitability variables have a significant positive effect on financial performance. But it is inversely related to activities that have no effect on financial performance.